Perancangan Visual Artwork Dengan Teknik Desain Pop Up Pada Board Game Untuk Media Pembelajaran Pencegahan Malnutrisi Untuk Usia 10 – 11 Tahun - Sutikno, Melinda Rachel; Prestiliano, Jasson; Pratiwi, Peni; Setiawan, Arie (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2023)
Lack of fruit and vegetable intake can cause malnutrition in the body because fruits and vegetables contain many important vitamins for body health. Children are reluctant to eat fruits and vegetables due to lack of awareness of healthy eating patterns. In this problem, children need to be given education, namely board game learning media for the prevention of malnutrition entitled